2011
DOI: 10.1021/jp111590s
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Vibrational State-Selected O2+ Ions in the B2Σg¯ State Using Threshold Photoelectron–Photoion Coincidence Velocity Imaging

Abstract: Using the recently developed threshold photoelectron-photoion coincidence (TPEPICO) velocity imaging mass spectrometer (Tang et al. Rev. Sci. Instrum.2009, 80, 113101), dissociation of vibrational state-selected O(2)(+)(B(2)Σ(g)(¯), v(+) = 0-6) ions was investigated. Both the speed and angular distributions of the O(+) fragments dissociated from individually vibronic levels of the B(2)Σ(g)(¯) state were obtained directly from the three-dimensional time-sliced TPEPICO velocity images. Two dissociation channels,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…Clearly, further experiment is desirable in order to shed light into this problem. We also remark that the smallness of the recently measured β asymmetry parameter by Tang et al [33] strongly suggests that the lifetime of B 2 Σ − g state is larger than the rotational period. However, an earlier measurement by Evans et al [34] suggests a lifetime of only about 0.4 − 2 ps, whereas Richard-Viard et al [35] found a rather long lifetime of about 70 ns.…”
Section: Three-channel Calculations With Population Redistributionmentioning
confidence: 56%
“…Clearly, further experiment is desirable in order to shed light into this problem. We also remark that the smallness of the recently measured β asymmetry parameter by Tang et al [33] strongly suggests that the lifetime of B 2 Σ − g state is larger than the rotational period. However, an earlier measurement by Evans et al [34] suggests a lifetime of only about 0.4 − 2 ps, whereas Richard-Viard et al [35] found a rather long lifetime of about 70 ns.…”
Section: Three-channel Calculations With Population Redistributionmentioning
confidence: 56%
“…Therefore, the real image needed to be handled prior to extracting speed and angular distributions through a multistep data reduction scheme including subtracting the false coincident events and deconvolution. Its details have been described in refs . Thus, the modified image of O + dissociated from the O 2 + ( 2 Σ u – ,v + =0) ion at 20.353 eV is shown in Figure b.…”
Section: Resultsmentioning
confidence: 99%
“…The β values for the 2 Σ u – state are kept at ∼0.4 for the lowest dissociation channel, except the v + = 5 state of 2 Σ u – , which is seriously influenced by the quasi-resonant v + = 4 state of B 2 Σ g – . According to the fact that the β values of dissociation of the B 2 Σ g – state are near 0.25, predissociation of the 2 Σ u – state along the lowest channel is faster than that of the B 2 Σ g – state.…”
Section: Resultsmentioning
confidence: 99%
“…The translational energy release in the dissociation of small ions by ion imaging has been used to great advantage mostly by the group of Zhou. 113,117,118 The analysis of the ion images was greatly simplified by the application of time sliced imaging in which only the ions ejected perpendicular to the extraction axis are collected by a multichannel plate detector followed by a phosphor imaging system. Consider the dissociation of a diatomic ion to a single dissociation channel with a single translational energy.…”
Section: Threshold Electron Detection In Coincidence With Imaged Ion mentioning
confidence: 99%